UK nuclear waste finding a way forward, One Great George Street COnference Centre, Westminster, London, 12 April 2000. (British Energy Society, 2000)
Speakers at this conference covered topics such as principles of stakeholder dialogue and some practical experience, consensus conferences of radioactive waste management, geological emplacement, high level waste and spent fuel, and the problem of consensus for society and science.